PENGARUH EDUKASI GERAKAN 1000 HPK TERHADAP PERBAIKAN POLA MAKAN IBU HAMIL RISTI DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KOTA SEMARANG - Pratama, Andriana Putri; Riyanti, Emmy; Cahyo, Kusyogo (Fakultas Kesehatan Masyarakat, 2017)
The 1000 FDL movement is an accelerated movement of nutrition improvement in pregnant women, lactating mothers, and children aged 0-23 months. The aim of this research to analyze the influence of education of 1000 FDL Movement on improvement dietary pattern of high-risk pregnant women in Puskesmas Kedungmundu, Semarang.The study used quasy experiments of non-equivalent control group design. The samples were high-risk pregnant women in working area of Puskesmas Kedungmundu, Semarang used total sampling counted 76 respondents. Data analysis used paired T Test for normal data and Wilcoxon for abnormal data with alpha 0.05.The results showed that in experimental group still have knowledge of less (60,5%), but already have support attitude (55,3%), good eating habits (55,3%), and good nutrient intake (57,9% %). While the control group still have knowledge of less (63,2%), but already have support attitude (60,5%), good eating habit (55,3%), and good nutrition (57,9% ). The bivariate test results showed significant differences in knowledge, attitudes, and dietary practices in the experimental group, and there was no significant difference in knowledge, attitudes, and dietary practices in the control group. MANOVA test results showed that education had a great effect on knowledge with R square 0,873 and 0,677 on attitude, and given enough effect on eating habit with R square 0,087 and 0,076 on nutrient intake.It is recommended that Health Office collaborate with Puskesmas to educate husband supporting the improvement of dietary pattern of high risk pregnant women and recommend the variance of balanced nutritious food consumption.